Characteristics of Interdisciplinary Islamic Studies Approach - Syofrianisda, Syofrianisda; Julhadi; Hanafi, Abdul (Al-Mudarris, 2025)
A Muslim, before practicing all its teachings, it is very important to really understand Islam. There are several methods or approaches that can be used in studying Islamic studies. This Islamic studies approach is a way or method used to study and understand Islam in depth. This research aims to analyze what approaches are used in studying Islamic studies. This research uses a qualitative method with a case study approach (case study design). The case study approach is a form of qualitative research based on understanding and human behavior based on human opinion. The results showed that there are six approaches to Islamic studies, namely: i) normative approach, ii) semantic approach, iii) philological approach, iv) hermeneutic approach, v) discourse approach, vi) historical approach. Islamic studies approaches are very important to learn and know. Because as Muslims we must be able to know about Islamic understandings using approaches and how to apply them to life. The results of this study can be used as initial data for subsequent researchers in studying this problem in different contexts and issues.